EFFECTS OF SERPENTINIZATION ON THE LITHOSPHERIC STRENGTH AND THE STYLE OF NORMAL FAULTING AT SLOW-SPREADING RIDGES - Escartin J.; Hirth G.; Evans B. (My University, 1997)
Rock deformation experiments indicate that serpentinization can strongly influence the strength and tectonics of the oceanic lithosphere. Strength versus depth profiles, calculated for conditions appropriate for slow-spreading ridges, indicate that the presence of serpentinite can reduce the integrated strength of the lithosphere by up to 30%. Results from flexural fault models indicate that if serpentinization is isolated to fault zones, strain localization should be enhanced, providing an explanation for the variations in the style of normal faulting along slow-spreading ridge segments. At segment centers, where serpentinites are scarce, deformation is accommodated on closely spaced faults with small throws. At the segment ends, where serpentinites are most abundant, faults are widely spaced and have large throws.
Keywords: MID-OCEAN RIDGES; DEFORMATION; SERPENTINIZATION; LITHOSPHERE; NORMAL FAULTS